(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article analyzes the agrotechnological and technical aspects of pre sowing soil tillage in the process of preparing agricultural crops for sowing. The relevance of developing and applying wide-coverage agricultural machines with high productivity, quality of operation, and energy- and resource-saving characteristics in global and national agriculture is substantiated. Agrotechnical measures performed in different regions with diverse natural-climatic and soil-meliorative conditions, as well as the types of machinery used and their operational features, are described. In particular, the interaction of chisel cultivators and toothed harrows with soil,